2019
DOI: 10.1007/s10404-018-2180-z
|View full text |Cite
|
Sign up to set email alerts
|

A micro-needle induced strategy for preparation of monodisperse liquid metal droplets in glass capillary microfluidics

Abstract: Monodisperse micro-sized liquid metal droplets have received considerable attention for developing flexible electronics, microfluidics actuators and reconfigurable devices. Herein we report an innovative and efficient strategy for large-scale preparation of Galinstan liquid metal microdroplets with controllable sizes using a micro-needle induced glass capillary microfluidic device. By inserting a stainless steel micro-needle into the inner liquid metal phase in the glass capillary, the hydrodynamic instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The weight ratio of glycerol and 5% PVA aqueous solution was 10:2.9. Therefore, the dynamic viscosity for the two-phase fluids were defined as 0.044 Pa•s and 0.002 Pa•s at room temperature [31], respectively. The interfacial tension between the liquid metal and the glycerol aqueous solution was 0.534 N/m [28].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The weight ratio of glycerol and 5% PVA aqueous solution was 10:2.9. Therefore, the dynamic viscosity for the two-phase fluids were defined as 0.044 Pa•s and 0.002 Pa•s at room temperature [31], respectively. The interfacial tension between the liquid metal and the glycerol aqueous solution was 0.534 N/m [28].…”
Section: Methodsmentioning
confidence: 99%
“…The two inner capillaries were concentric aligned with axial spacing of 100 µm, and the metallic needle was inserted into the inlet capillary along the axis of the orifice, with a transverse distance between the micro-needle tip and the center of the capillary orifice of 175 µm. The detailed dimensions and fabrication processes of the micro-needle induced co-flowing glass capillary microfluidic device could be obtained in our previous published paper [31]. The glycerol and liquid metal were supplies separately by two microsyringe pumps (Harvard Apparatus, Holliston, MA, USA) equipped with gastight precision glass syringes (Hamilton, Bonaduz, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, there still lacks a generalized way to make as desired liquid metal based materials with even lighter density according to various needs. Fortunately, recent research has found that the existence of the oxide is of great help on the combination of eGaIn with other materials, especially silica, [ 40,41 ] metal particles, [ 42,43 ] and polymers. [ 44,45 ] Therefore, we found that the promising answer might lie in the development of composite materials.…”
Section: Introductionmentioning
confidence: 99%